Application of Insulating Gels in Highly Mineralized Petroleum Waters (Journal of Pedagogical Inventions and Practices, 2023)
It is known that oil reserves in any oil fields are limited. As a result of continuous oil extraction, the amount of oil in the fields decreases and the amount of water increases. As a result, the percentage of water in the oil liquid extracted from wells increases to 90-95%, and the volume percentage of oil decreases to 10-5%. Due to the costs of separating water and oil and cleaning them, some wells do not produce economic results despite the quantity of oil.